SOSIALISASI INITIAL ASSESMENT PRA ANESTESI KEPADA DINAS KESEHATAN PROVINSI NTB SEBAGAI STRATEGI DALAM UPAYA PENCEGAHAN KOMPLIKASI ANESTESI PADA PELAYANAN BEDAH MAYOR DI RSUD PROVINSI NTB - Atik Setiawan; Lalu Simbawara; Elya Endriani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Pre-anesthetic initial assessment is a key element in anesthetic risk management, particularly in major surgical patients with high clinical complexity. Variability in the implementation of initial assessment and limited understanding among policy stakeholders may reduce the effectiveness of preventing anesthetic complications. Within the framework of regional health service governance, the Health Office plays a strategic role as a regulator in ensuring the standardized implementation of pre-anesthetic initial assessment oriented toward patient safety.This activity aimed to improve the understanding of staff of the West Nusa Tenggara Provincial Health Office regarding the concept and role of pre-anesthetic initial assessment as a foundation for strengthening anesthetic service governance at the West Nusa Tenggara Provincial General Hospital. This community service activity was conducted in the form of socialization sessions, including focused discussions and knowledge evaluation through pre-test and post-test. A total of ten staff members of the West Nusa Tenggara Provincial Health Office participated in this activity. The results showed an improvement in participants knowledge levels from poor to good knowledge following the educational intervention. This improvement reflects a more comprehensive understanding of the function of pre-anesthetic initial assessment as an instrument for preventing anesthetic complications, as well as a basis for guidance and supervision of health service quality. It can be concluded that strengthening the Health Office’s understanding of pre-anesthetic initial assessment has the potential to serve as a governance foundation for supporting the development of an initial assessment–based model to prevent anesthetic complications in major surgical patients.